2022
DOI: 10.1002/adma.202106692
|View full text |Cite
|
Sign up to set email alerts
|

Nanophotonic Materials for Twisted‐Light Manipulation

Abstract: Twisted light, an unbounded set of helical spatial modes carrying orbital angular momentum (OAM), offers not only fundamental new insights into structured light–matter interactions, but also a new degree of freedom to boost optical and quantum information capacity. However, current OAM experiments still rely on bulky, expensive, and slow‐response diffractive or refractive optical elements, hindering today's OAM systems to be largely deployed. In the last decade, nanophotonics has transformed the photonic desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 107 publications
0
24
0
Order By: Relevance
“…Furthermore, it has been of great interest to shape and engineer quantum sources, that is, structured light. [309] For instance, Chen et al reported epitaxial-QD based on-chip sources that generates single photons with arbitrary orbital angular momentum. [76] The epitaxial-QD is coupled with microring resonators of which the inner walls are patterned to make angular grating components.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been of great interest to shape and engineer quantum sources, that is, structured light. [309] For instance, Chen et al reported epitaxial-QD based on-chip sources that generates single photons with arbitrary orbital angular momentum. [76] The epitaxial-QD is coupled with microring resonators of which the inner walls are patterned to make angular grating components.…”
Section: Discussionmentioning
confidence: 99%
“…[95,96] In recent years, on-chip nanophotonics based on various metasurfaces has provided the route for manipulating OAM in real space, momentum space, and the spatiotemporal domain, while dispensing with bulky and expensive traditional optical components. [95,96] In this context, introducing QE-coupled metasurfaces can open a new avenue for on-chip realization of OAM-encoded single-photon emission.…”
Section: Molding Polarized Emissionmentioning
confidence: 99%
“…Ting Wang, Weiqing Chen, Hok-Leung Loi, Wei Gao, Xuhui Xu,* Longhui Zeng, Ping Kwong Cheng, Safayet Ahmed, Xue Yu, Feng Zhao, Jianbei Qiu, Feng Yan, Siu Fung Yu,* and Yuen Hong Tsang* DOI: 10.1002/adom.202200439 of different functional nanowires that perform the generation, transmission, manipulation, and detection of light on a common platform. [1][2][3] Extensive investigations on the physical and structural properties of nanomaterials have boosted the rapid development of nanowire-based photonic devices for various applications. [4,5] At present, there are two main methods for integrating nanowires with on-chip optical waveguides: direct growth of semiconductor nanowires on the passive waveguide material or mechanical transfer of nanowires from their growth substrate to the target devices.…”
Section: Stable Single-mode Lasing From a Hybrid Perovskite-polymer F...mentioning
confidence: 99%